IMPROVING THE TECHNOLOGY OF TEACHING MEDIA ETIQUETS AND TECHNOETHICS IN PRIMARY EDUCATION (Scientific journal of the Fergana State University, 2024)
The article emphasizes the necessity of teaching information technologies as a subject in primary education, media etiquette and ethics of utilizing information devices that is considered to be compulsory in this fast paced development. In this article opportunities of internet, its role in teaching is analyzed, effective methodological techniques, and methodical recommendations are suggested with the aim of defending students from online violence and threat. In order to attain consistency and efficiency, the importance of parental cooperation, improvement of teachersʼ and studentsʼ technological competence have been considered, in regard certain scientific-methodical recommendations have been drafted.